Evidence from lithic weapons - (:unkn) unknown (My University, 2019)
Genetic, fossil, and archaeological evidence strongly support an African origin for modern humans (Homo sapiens) perhaps ~200,000-300,000 years ago (~200-300 ka). Subsequent dispersals is found as early as 190-170 ka in the Near East while China is reached by 80 ka ago and Australia by 65 ka. European colonization comes much later after 44-42 ka. These processes led to the serial extinction of other non-African hominin groups such as the Neanderthals. Determining the reasons for the evolutionary success of H. sapiens and tracing the pathways of their dispersal out of Africa remain central themes of paleoanthropological investigation. Our own actual researches on Ksar Akil (Lebanon) collections stored in Harvard University’s Peabody Museum of Archaeology and Ethnology, suggests that some of the answers to these questions can be found there on the rich lithic industries (>38,000 artifacts from the 1947-1948 excavations) largely unstudied until now. These researches conducted to direct comparisons with Grotte Mandrin layer E industries in the western shores of the mediterranean basin and that show remarkable technical similarities with Ksar Akil layers XXV-XXII, in the first phase of the Initial Upper Paleolothic. These data suggest a far earlier human dispersals around the Mediterranean basin in Western Europe. A close functional analysies of Mandrin E lithics, obtained by the most modern archeological methods, shows that these industries were related to the use of the bow and arrow, a major technological innovation which fundamentally changed human hunting practices and the nature of inter-group interactions. The link highlighted between Mandrin E and Ksar Akil IUP suggest the existence of initial incursions for modern humans into Europe via the Rhone Valley, incursions that could have been made possible by the mastery of the bow and arrow. That first migration may have, at least initially, failed to displace local Neanderthal populations.
Keywords: African Research